1986
DOI: 10.1111/j.1600-0722.1986.tb01381.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the adhesion of bacterial layers to some restorative dental materials

Abstract: — In the present study a powerful method for measuring adhesion is introduced. It is, based on the observation that the bacterial layer is usually capable of maintaining an interior pressure, but fractures when this pressure exceeds a certain critical value characteristic of the mechanical and adhesive properties of each specific bacteria and its formed matrix. A water jet: from a nozzle was directed on the bacterial layer of the specimen. A specimen covered with a layer of Streptococcus mutans, grown in an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…A similar tendency has been reported in in vitro conditions as well. 26 Contrary to our findings, no significant difference was found between bacterial adhesion to Co/Cr alloy and denture base polymer in a study conducted on implant materials. 27 The experimental conditions and the S. mutans strains used in that and the present study, however, were different.…”
Section: Discussioncontrasting
confidence: 83%
“…A similar tendency has been reported in in vitro conditions as well. 26 Contrary to our findings, no significant difference was found between bacterial adhesion to Co/Cr alloy and denture base polymer in a study conducted on implant materials. 27 The experimental conditions and the S. mutans strains used in that and the present study, however, were different.…”
Section: Discussioncontrasting
confidence: 83%
“…Oral bacteria must then interact with these salivary components in order to adhere to the surface. Important factors which foster the accumulation of dental plaque to smooth hard surfaces, are surface characteristics (Tullberg, 1986;Yamauchi et al, 1990). The effect of surface roughness on bacterial adherence is complex.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Yamauchi et al (1990) found that S. mutans adhered better to smooth surfaces. Tullberg (1986) reported that polishing increased the adhesion capacity of gold and polymethyl metacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…The finish of the restoration, the superficial roughness and its integrity, as well as the physiochemical properties of the material, can influence the build-up of dental plaque. 18,[54][55][56] For the samples with surface finishing, the contact angle data showed higher wettability values. As shown in a previous study, 57 the topography of the material surface, including the surface of Ariston pHc, is noticeably different with and without finishing, including superficial roughness.…”
Section: Discussionmentioning
confidence: 99%